2020
DOI: 10.1515/jbcpp-2019-0076
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin modulates granulosa cell mRNA androgen receptor gene expression in dehydroepiandrosterone-induced polycystic ovary in Wistar rats via metabolic and hormonal pathways

Abstract: BackgroundIt is estimated that about 5–10% of women suffer from polycystic ovarian syndrome (PCOS) which is a major cause of female reproductive dysfunction. This study examined the role of quercetin on dehydroepiandrosterone (DHEA)-induced PCO in Wistar rats.MethodsTwenty-eight pre-pubertal female Wistar rats that are 21 days old weighing 16–21 g were sorted into four groups (n = 7). Group I served as control and was given distilled water only, Group II were injected with 6 mg/100 g BW of DHEA in 0.2 mL of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…However, the regulation of estrogen expression by QUR is still controversial. Contrary evidence [ 17 , 19 , 20 ] suggests that QUR reduces PCOS estrogen levels. This may be because estrogen is not always expressed too high or too low in PCOS and QUR may regulate estrogen, which is worth further investigation.…”
Section: Effect and Mechanism Of Quercetin In Polycystic Ovary Syndromementioning
confidence: 96%
See 1 more Smart Citation
“…However, the regulation of estrogen expression by QUR is still controversial. Contrary evidence [ 17 , 19 , 20 ] suggests that QUR reduces PCOS estrogen levels. This may be because estrogen is not always expressed too high or too low in PCOS and QUR may regulate estrogen, which is worth further investigation.…”
Section: Effect and Mechanism Of Quercetin In Polycystic Ovary Syndromementioning
confidence: 96%
“…In two in vivo experiments [ 17 , 19 ], QUR inhibits androgen receptor expression in the ovaries of rats with polycystic ovary syndrome induced by dehydroepiandrosterone (DHEA). Zheng S et al [ 17 ] reported that QUR may reduce AR expression by affecting the combination of AR in specific sequences of C-type natriuretic peptide (CNP) and natriuretic peptide receptor 2 (NPR2) gene promoters.…”
Section: Effect and Mechanism Of Quercetin In Polycystic Ovary Syndromementioning
confidence: 99%
“…For example, Khorshidi et al observed that supplementation of 1,000 mg/day quercetin for 12 weeks significantly decreased testosterone, fasting blood glucose, insulin, and homeostatic model assessment of insulin resistance of PCOS patients compared with the placebo group [ 48 ]. Quercetin alleviated the PCOS by suppressing the levels of inflammatory cytokines (IL-1 β , IL-6, and tumor necrosis factor α ) [ 49 ], increasing the activity of antioxidant enzymes (superoxide dismutase, catalase, glutathione-S-transferase, and reduced glutathione) and improving granulosa cell apoptosis (upregulation of Bcl-2 and downregulation of Bax) [ 50 ]. In this study, we predicted that quercetin targeted PLK1, TXNIP, and MAP3K14.…”
Section: Discussionmentioning
confidence: 99%
“…The changes in adiponectin, adiponectin and resistin in adipose tissue induced by PCOS were also reversed to a certain extent [ 85 ]. After quercetin treatment, the following changes occurred in the rats with PCOS induced by dihydrotestosterone: the activity of progesterone, metabolic enzymes and antioxidant enzymes was significantly increased, and DHEA-induced morphological changes related to polycystic ovaries were alleviated [ 87 ]. Quercetin also significantly decreased the expression of testosterone (T), estradiol (E(2)), LH, Bax, IL-1β, IL-6 and TNF-α, increased the expression of FSH and Bcl-2, and inhibited the expression of AR.…”
Section: Overview Of the Role Of Sirt1 In The Treatment Of Pcosmentioning
confidence: 99%